Turning responsible purchasing and supply into supply chain responsiveness. Issue 9 (21st October 2019) - Yang, Jie; Xie, Hongming; Yu, Guangsheng; Liu, Mingyu
Abstract : Purpose: The purpose of this paper is to investigate whether responsible purchasing (relational commitment and supplier evaluation) and responsible supply (supplier firm information sharing and supplier performance) affect the two factors of supply chain responsiveness including process efficiency and customer knowledge management capability, which, in turn, affect other three factors of supply chain responsiveness, such as dyadic quality performance, innovation capability and buyer‒supplier relationship improvement. Design/methodology/approach: This study used questionnaire survey and statistical analytical methods. Employing path analysis, this study tested hypothesized relationships using data collected from manufacturers. Findings: The findings of this study support the theorized links. Responsible purchasing and supply enhance supply chain responsiveness, which is reflected through process efficiency, customer knowledge management capability, dyadic quality performance, innovation capability and buyer‒supplier relationship improvement. Originality/value: Grounded in the goal interdependence theory, this study investigates the effects of responsible purchasing and supply on supply chain responsiveness in the context of Chinese manufacturers. This study offers managerial implications and theoretical contribution.